THE EFFECT OF SERVICE QUALITY IN ONLINE DELIVERY ORDER (DO) COMPLETION ON CUSTOMER SATISFACTION AT PT. CONTAINER MARITIME ACTIVITIES - Selasdini, Vidya; Nurdin, Muhammad; Budi Nugroho, Arief (Dinasti International Journal of Digital Business Management, 2021)
Indonesia as a maritime country where sea transportation plays an important role and strategic position in mobilizing the movement of goods and services, where international trade activities in this case exports and imports use sea transportation. PT. Container Maritime Activities (CMA) Indonesia, based in Jakarta, is an agency shipping company engaged in container shipping, in other words, having its own containers. In economic activity, it cannot be separated from the import process, because imports are a reflection of a country's economic sovereignty, whether goods and services made in the country are still the masters in their own country. A country imports because it experiences a deficiency (lack/failure) in carrying out the production of goods and services for the consumption needs of its population. In this case the Delivery Order (DO) document is required by the importer to remove the goods from the container terminal terminal